Trends in global and national infertility and factors associated with primary infertile couples in recent middle-aged Chinese - Huancheng Tang; Jun Yang; Zeshen Wu; Biao Jiang; Wei Sun; Chaoyang Zhang; Zhi Hu; Qiao Fu; Wei Zhang; Siyu Zhang (PLoS ONE, 2025)
Background Infertility poses a significant burden on both global and national scales. However, the epidemiology of primary infertility among reproductive-aged couples in China remains poorly understood. Therefore, this study aimed to investigate the global infertility rate and identify factors associated with primary infertility among middle-aged couples in China. Methods Cross-sectional data were derived from the Global Burden of Disease (GBD) study and the Chinese Health and Retirement Longitudinal Study (CHARLS), two extensive databases that examined various disease burdens and associated factors at both global and national levels. Results From 1990 to 2019, the global infertility population has shown a steady annual increase. In China, the age-standardized prevalence rate of infertility has remained relatively stable over the past three decades. However, this rate was notably higher than the global age-standardized infertility prevalence rate. Our analysis revealed that the prevalence of primary infertility among middle-aged Chinese couples was approximately 1.7% (947,953/56,892,517). Additionally, we identified anxiety as an associated factor with infertility, highlighting the need for increased public attention to mental health in China. Conclusions Infertility continued to be a pressing issue on both global and national levels. This situation warranted widespread attention from Chinese policymakers and healthcare managers. The findings might guide future policy-making and medical interventions in China, with a particular focus on supporting the reproductive needs of middle-aged individuals.